Empowerment and Innovation of Peasants in Nisam District, Aceh Utara - Alfian; Nazaruddin; Defi Irwansyah (Budapest International Research and Critics University, 2021)
This research was conducted to examine the impact of empowering and fostering innovation of peasants as an activity that summarizes the values to build a new paradigm in agricultural development. The role of the agricultural sector is very strategic, not only in order to achieve food self-sufficiency but also in order to expand non-oil and gas foreign exchange sources. The purpose of this study is to see the impact of the strategy and pattern of relations between the Aceh Community Empowerment Institution (LPMA) in implementing the empowerment program and fostering farmer innovation in Nisam District, North Aceh Regency. The method used in this study is a qualitative method with data collection techniques through interviews, observation and documentation. The phenomenon of poverty for the people in Nisam District, North Aceh generally comes from the agricultural sector due to the lack of support for knowledge and business capital. This empowerment activity is carried out by the Aceh Community Empowerment Institute (LPMA), a non-governmental organization. Research shows that the optimization of empowerment and innovation carried out by LPMA has contributed to increasing community empowerment and also contributed to business partnerships for poor farmers to increase community empowerment.